Comment: Marrying Functional Differentiation and Institutional Economics: Reflections on Steffen Roth's Article. Issue 4 (2nd October 2017) - Valentinov, Vladislav
Abstract: The Luhmannian idea of functional differentiation offers a novel and radical systems-theoretic framework reinforcing the institutionalist vision of the embeddedness of the economic system in the societal and natural environment. Reflecting on Steffen Roth's article, I formulate two complementary arguments. The first is that any self-organized complexity can be supported by the installation of a systemic boundary protecting it from the outer environment. The second is that this boundary prevents the complexity of the outer environment from being fully translatable into the intra-systemic complexity. Both arguments potentially inform the institutionalist analysis of the operational and moral problems of the economic function system.